1999
DOI: 10.4315/0362-028x-62.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Aeromonas Species Isolated from Processed Channel Catfish

Abstract: From August 1994 to May 1995, 238 channel catfish fillets collected from three processing plants in the Mississippi Delta at four time periods were tested for the presence of Aeromonas species. Identification of Aeromonas spp. was accomplished using an automated Vitek bioassay system with gram-negative and nonfermenter cards. Approximately 36.1% were positive for A. hydrophila, 35.7% for A. sobria, and 10.9% for A. caviae. All three Aeromonas spp. were found in all three processing plants, and the incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 0 publications
2
25
0
1
Order By: Relevance
“…All strains in our study were sensitive to gentamicin at concentrations of ≤4 µg/mL. Other researchers (Wang & Silva, 1999;Vila et al, 2002;Hatha et al, 2005;Ottaviani et al, 2006;Awan et al, 2009) have also confirmed that A. hydrophila was sensitive to gentamicin. Unlike us, Thayumanavan et al (2003) showed a resistance to gentamicin (3.6%).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…All strains in our study were sensitive to gentamicin at concentrations of ≤4 µg/mL. Other researchers (Wang & Silva, 1999;Vila et al, 2002;Hatha et al, 2005;Ottaviani et al, 2006;Awan et al, 2009) have also confirmed that A. hydrophila was sensitive to gentamicin. Unlike us, Thayumanavan et al (2003) showed a resistance to gentamicin (3.6%).…”
Section: Discussionsupporting
confidence: 63%
“…could grow and release enterotoxin and haemolysin at fridge temperature conditions (Sharma & Kumar, 2011). A number of researchers have confirmed the presence of β-haemolytic aeromonads in fish products (Tsai & Chen, 1996;Wang & Silva, 1999;Radu et al, 2003;Thayumanavan et al, 2003;Yuсel et al, 2005;Erdem et al, 2010). A special attention is paid on A. hydrophila as a causative agent of foodborne gastroenterites, and fish products as the commonest vector of this microbial pathogen (Thayumanavan et al, 2003;Hatha et al, 2005;Paniagua et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens are mostly isolated from; rivers, lakes, sewers, clorinated drinking water (1,5,12,17,24,25,31), retail fresh vegetables (33), sea foods (1, 2, 17), red and minced meat (10,22,26,29,37), raw and pasteurized milk (21,35), unpasteurized cheese (34). It is also widespread in fresh water fishes (14,28,40). There are only limited studies on determination of motile Aeromonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of A. hydrophila in fish samples investigated in this study was lower in comparison to those detected in U.S. by Wang & Silva (1999) Nagar et al (2011) stated the presence of A. hydrophila in 3.85% of 52 freshwater fish samples. In the current study, the incidence of A. hydrophila in fish was 3.75%.…”
Section: Discussionmentioning
confidence: 54%